تحسين تحمل البطاطا (Solanum tuberosum) للإجهاد الملحي باستخدام التطفير الكيميائي - خوجة حسان; رجب مازن; متوج وائل (Latakia University Journal -Biological Sciences Series, 2017)
طفرت كيميائياً درنات من صنف البطاطا مارفونا بتراكيز (20،30،40) mM من مادة الايتيل ميتان سلفونات EMS، وبثلاثة أزمنة غمر (2،3،4) ساعة خلال عام 2013؛ لتحسين تحمل البطاطاL. Solanum tuberosum للملوحة. جرى زراعة نباتات منتخبة طافرة (5M) للصنف مارفونا وغير طافرة من أصناف مارفونا، سبونتا وفلوكا عام 2015، وعرضت النباتات لضغط انتخابي بريها بماء محتو كلوريد الصوديوم بتراكيز من 0 إلى 200 ميللي مول، أدت الزيادة التدريجية في تراكيز الـ Nacl إلى انخفاض معنوي في أغلب الصفات الخضرية وصفة الإنتاج؛ فقد تراوح طول النبات من 68 إلى 41 سم، وعدد الأوراق من 21 إلى 12 ورقة، وتراوح قطر الساق من 1.349 إلى 0.370 سم، وتراوحت المساحة الورقية بين 234.9 إلى 85.4 سم2.؛ تباينت النباتات الطافرة للصنف مارفونا مع غير الطافرة و صنفي سبونتا وفلوكا بقدرتها على إنتاج درنات حيث تراوح عدد الدرنات بين 9.3 و .2.8 درنة، ووزن الدرنات/نبات من740 إلى 155 غرامًا، ومتوسط وزن الدرنة من 75.2 إلى 24.6 غرامًا. بينت النتائج بان هناك تباين في مدى تحمل هذه المعاملات للإجهاد الملحي حيث كان المعاملة 4T3P2 أكثر تحملاً Marfona cultivar were chemical mutagen using 20, 30 and 40 mM of Ethyl Methane Sulphonate (EMS) for 2, 3, 4 hrs in 2013. was conducted to improve potato (Solanum tuberosum L.) tolerance to salinity. Plants Marfona mutagen from M5 and unmutagen were cultured with Spunta and Falouka Cvs in 2015. Plants were later subjected to another selection pressure, by irrigating them using water containing Nacl between 0-200 mM The results showed that the gradual increase in Nacl concentrations caused a significant gradual decreases in most vegetative, yield and its component characteristics. Mutant plants varied with unmutant for Marfona, Spunta and Falouka in plant height varied from 68 to 41 cm and number leaves varied from 21 to 12 leaf. and stem diameter varied from 1.349 to 0.370 cm and leaf area varied from 235 to 84 cm2. However, produced tubers number varied from 9.3 to 2.8 and weight them from 740 to 155 grams and tuber weight from 75.2 to 24.6 grams. The results also showed variations in the extent of tolerance between studied treatments to salinity stress where 4T3P2 treatment was the most tolerant.